Kajian Kesesuaian Wisata Pantai Kategori Rekreasi di Pantai Rambak Kabupaten Bangka Provinsi Kepulauan Bangka Belitung - Bernia, Rika Kristi; Adibrata, Sudirman; Farhaby, Arthur Muhammad (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2024)
Rambak Beach is one of the beaches in Jelitik Village, Sungailiat District, Bangka Regency. It is approximately 10 kmfrom Sungailiat Cite Center 30 km from Pangkalpinang. This research was conducted in Juni 2022 at Rambak Beach,Bangka Regency. Measurement of suitability parameters for beach tourism was carried out at three stations using thepurposive sampling method. The parameter meausurements carried out obtained the research results of the suitabilityIndex Value for the Tourism Category for beach recreation,namely getting a result of 99% and the Tourism Category forbeach recreation, namelly getting a result of 92 %,. Included in the S1 (category appropriate). The results show that thecarrying capacity of tourist activity areas on land for beach recreation is around 2,467 people a day, while for swimmingactivities it is 412 people a day and has not exceeded the area’s carrying capacity limit for carrying out tourist activities.